Digital media, friendships and migrants' entangled and non-linear inclusion and exclusion. (December 2022) - Bork-Hüffer, Tabea
In this article, I shed light on the role of digital media and friendships in migrants' inclusion and exclusion. Connecting the empirical findings of a qualitative, non-media centric, multi-method study to existing research in digital migration studies, digital media and friendship as well as the literature on inclusion and exclusion, I propose the concept of entangled inclusion and exclusion. This perspective underlines migrants' continuous (re-) negotiations of their situatedness in the (trans-)local spaces of the places they come from, move to and through. While playing diverse roles in migrants' development and maintenance of (trans-) local friendships, digital media contribute to non-linearities in migrants' subjective feelings of being included or excluded, making the processes involved more complex while also serving as material and symbolic signifiers of entangled inclusion and exclusion.